Cutting Tools in Finishing Operations for CNC Rapid Manufacturing Processes: Simulation Studies - M. Nafis, O. Z.; Case, Keith; Watts, Darren (Hampshire Press Ltd., 2014)

(untitled)
Over the years, CNC machining has been widely used in producing metal parts with high accuracy and reliable quality. A distinct process planning approach that utilizes an indexing device to hold the workpiece has extended CNC applications into the realm of rapid manufacturing (CNC-RM) processes. This study improves the implementation of this technology by providing a methodology for integrating the tools into finishing processes. It aims to enhance the process efficiency by minimizing the stair-casing effect of layer removal and so improve the quality of machined parts. In order to achieve this, finishing operations are executed using different types of end mill tools to cater for specific surfaces on parts. Several simulations are carried out to verify the method and implications. The present findings indicate the advantages of the developed approach in terms of cutting time and the minimisation of excess volumes left on parts. It is shown that using different cutters for finish cuts will improve the capabilities of CNC machining in rapid manufacturing applications.